TEACHERS AS AGENTS OF CHANGE: THE ROLE OF HUMAN RESOURCE MANAGEMENT IN DEVELOPING TEACHER PROFESSIONALISM IN ISLAMIC SCHOOLS - Selayuni, Nur; Afina, Afina; Habib, Syafaatul (International Journal of Multidisciplinary Reseach, 2025)
Teachers have a strategic role as agents of change in Islamic education, by strengthening the character and spiritual values of students. This research aims to examine the role of teachers as agents of change in Islamic schools, as well as analyze the concept of human resource management (HRM) in Islamic education. This research uses a qualitative approach with a literature review method, which aims to analyze various relevant literature sources. The main focus of this research is to identify strategies for developing teacher professionalism, challenges faced, and solutions in strengthening teacher human resources to improve the quality of education in Islamic schools. The problems raised are the low quality of teacher professionalism and the suboptimal management of human resources. The result of this research is that teachers have a strategic role in shaping superior generations through innovative, interactive and globally oriented learning. HR management in Islamic education must include strategic, professional, and spiritually valuable management. The development of teacher professionalism needs to be done through increasing competence, adaptation to change, and the quality of education in accordance with the demands of the 21st century. Strengthening teacher human resources in Islamic schools requires a sustainable strategy based on competence and Islamic values, in order to create a generation that is not only smart, but also has integrity.